2007
DOI: 10.1073/pnas.0700253104
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral prefrontal cortex and tactile memory disambiguation in the human brain

Abstract: Tactile sensory information is first channeled from the primary somatosensory cortex on the postcentral gyrus to the parietal opercular region (i.e., the secondary somatosensory cortex) and the rostral inferior parietal lobule and, from there, to the prefrontal cortex, with which bidirectional connections exist. Although we know that tactile memory signals can be found in the prefrontal cortex, the contribution of the different prefrontal areas to tactile memory remains unclear. The present functional MRI stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
51
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 47 publications
8
51
1
Order By: Relevance
“…However, the experiment was designed to test the hypothesis that the VLPFC is critical for the disambiguation of mnemonic traces when the relations between stimuli and their contexts are unstable [20][21][22][23]. Patients with lesions to the VLPFC were predicted to be selectively impaired on the unstable context retrieval condition which assesses active controlled retrieval.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the experiment was designed to test the hypothesis that the VLPFC is critical for the disambiguation of mnemonic traces when the relations between stimuli and their contexts are unstable [20][21][22][23]. Patients with lesions to the VLPFC were predicted to be selectively impaired on the unstable context retrieval condition which assesses active controlled retrieval.…”
Section: Resultsmentioning
confidence: 99%
“…This study tested the above predictions by examining the performance of patients with damage to the frontal cortex on three memory retrieval conditions, in which the level of ambiguity between stimulus items and their contexts was manipulated by varying the probability with which a stimulus (word) and a context (background) appeared in relation to one another [20][21][22][23]. Performance of patients with lesions to the frontal cortex was compared with that of patients with temporal lobe lesions that had involved the hippocampus and parahippocampal cortex, as well as healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies investigating the role of the prefrontal cortex in the auditory domain have focused on verbal phonological and semantic memory (23)(24)(25). The aim of the present study was to examine the hypothesis that the midventrolateral prefrontal cortex is involved in the active controlled retrieval of nonverbal auditory information from memory, in a manner analogous to its previously demonstrated role in the retrieval of verbal and nonverbal visual and tactile information (8,9,26).…”
mentioning
confidence: 94%
“…More precisely, it has been proposed that the two midventrolateral prefrontal cortical areas 45 and 47/12 are critical for the active selection and retrieval of information from memory when stimuli are related to other stimuli/contexts in multiple and more-or-less equiprobable ways, so that memory retrieval cannot be a matter of mere recognition of the stimuli or supported by strong and unique stimulus-to-stimulus or stimulus-to-context associations (7). In previous functional neuroimaging studies, we were able to show activity increases that were specific to the midventrolateral prefrontal cortex for the active retrieval of visual and tactile stimuli (8,9). A more recent study has shown that patients with lesions to the ventrolateral prefrontal region, but not those with lesions involving the dorsolateral prefrontal region, show impairments in the active controlled retrieval of the visual contexts within which words had appeared (10).…”
mentioning
confidence: 97%